3th European Quality of Life Survey Quality of life in Europe: Impacts of the crisis - Anderson, Robert; Dubois, Hans.; Leoncikas, Tadas; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2012)
The European Quality of Life Survey (EQLS) is an established tool for documenting and analysing quality of life in the EU. First carried out in 2003, the EQLS explores issues pertinent to the lives of European citizens, such as employment, income, education, housing, family, health, work-life balance, life satisfaction and perceived quality of society. The analysis looks at the relationship between subjective and objective measures, between reported attitudes and preferences on one side, and resources and living conditions on the other.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Living conditions -- European Union countries; Social surveys -- European Union countries; Quality of life -- European Union countries; Electronic books